EFEKTIVITAS PROGRAM CITY TOUR TERHADAP PENINGKATAN JUMLAH KUNJUNGAN WISATAWAN DI MUSEUM BALI DENPASAR - Hutagalung, Lidia Uli Christiani Karmelia; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA; Vol 3 No 1 (2015): VOL 3, NO 1 (2015): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i01.p07, 2015)
ABSTRACT This study discusses the effectiveness of the program in which the program Denpasar City Tour effect on the increase in the number of tourist arrivals. Denpasar City Tour program is one program that is offered to tourists to visit tourist destinations in the city of Denpasar. One of the areas that fall into the tourist destination Denpasar City tour is Bali Museum. This study aims to determine the effectiveness of the program Denpasar City Tour in increasing the number of tourist visits. Sources of data taken from one of the existing tourist tuuan the Bali Museum in Denpasar and Regional Tourism Office, with data collection techniques of observation, interviews, questionnaires, literature study. Sampling using accidental sampling, respondents were taken by 30 respondents. The data analysis technique used is descriptive qualitative. Results of this study can be concluded about the effectiveness of the program Denpasar City Tour is supported by the perception of tourists who visited Bali Museum in Denpasar and traveled through the attitude scale showed good enough category with an average of 3.28 and it can be seen from the increasing number of tourists visit to Bali from 2006-2011 with an average growth of 17,86% as well as visits to Bali Museum from 2009-2012 with an average growth of 7,36%. Based on the results of this study suggested that the implementation of Denpasar City Tour program remain to be implemented and necessary to improve promotional activities Denpasar City Tour Program to enhance cooperation with the private sector (BPW), as well as improve and build supporting facilities Denpasar City Tour Program.
Keywords: Effectiveness, Denpasar City Tour, Museum Bali